A Training Program to Improve IFSP/IEP Goals and Objectives Through the Routines-Based Interview - Boavida, T.; Aguiar, C.; McWilliam, R. A. (Topics in Early Childhood Special Education, 2014)
The authors describe a training program designed to improve the knowledge and skills of early childhood interventionists. Within the context of using the Routines-Based Early Intervention approach, this training focused on improving the quality of goals and objectives on individualized plans, through the Routines-Based Interview. We structured the training around five face-to-face sessions and a follow-up 3 months later. Here, we describe the development of the program, its content and methods, and the results on improvement of the goals and objectives with 80 professionals. These participants had completed the training, provided pretraining data, and provided posttraining data. Results showed that the training described here had the desired very large effect: Quality ratings of goals and objectives increased by over three standard deviations.